(untitled) (Environment & Health, 2017)
Background: Provision with safe household articles, including children’s one, is one of the main factors in the population health protection. The prevention of the negative impact of the unfavourable factors on human health connected with the production and appearance of the potentially unsafe products in Ukrainian market requires the revision of methodical approaches and scientific substantiation of the necessity of the use of the new indicators for hygienic assessment of modern textile goods. Objective: We established a degree of danger of separate kinds of clothes for children’s health and suggested a domestic hygienic classification on its basis. Materials and methods: We used the method of integral assessment that allowed us to determine the safety index for separate kinds of clothes. Results: According to the technology of the construction of integral assessments, the information indicators of safety of separate kinds of clothes were determined in the first stage of investigation (such as, percentage of square of direct skin contact, age of children, duration of direct contact with a skin for a day). The weight coefficients of these indicators were calculated in the second stage. Then the assessment scales for the gradation of their changes were developed for every indication. Taking into account the ranges of changes of the informative indicators, the children’s clothes were divided into 11 classes. Thus, a determination of the degree of the potential danger of the goods for the child’s organism is a background of the domestic classification of children’s clothes. The use of integral assessment method allowed us to determine the safety index of separate kinds of clothes depending on the square of direct skin contact with clothes, age anatomical-and-physiological features of child’s organism and duration of direct skin contact with clothes for a day. Conclusions: Suggested approach is a scientific provision of methodology of the hygienic expertise of children’s clothes. According to the hygienic classification, the safety index was established for every product. It determines a risk degree of its potential impact on children’s and adults’ health.